Concepts in Bioscience Engineering - Dods, Richard (Springer International Publishing : Imprint: Springer, 2019)
This textbook teaches bioengineers critical concepts about protein three dimensional structures, how proteins fold, and how the folding affects the functioning of the protein. Protein folding has profound effects on the discovery of biopharmaceutical drugs (especially the transport of immunological compounds to their site of action) as well as on tissue engineering. Dr. Dods covers topics in easily understood terms through the use of glossaries heading each chapter and footnotes and summaries at the end of each chapter. The chapters cover disordered proteins and large sequences of disorder that exists within proteins, secondary structure (α-helix and β-pleated structure), tertiary and quaternary structure, post-translational changes, proteopathies, bioengineering approaches used to study protein folding, and computer software for protein folding. For each of these topics the elements of biomolecular imaging, cellular and tissue engineering, and health care systems engineering are built. Molecular engineering concepts such as site-directed mutagenesis are addressed. For reinforcement of the concepts presented in this text, activities and problems (Queries) are included in the chapter. Introduces the folding of proteins as an aspect of bioscience engineering in simple, understandable language Supports readers' ingestion of more-challenging ideas with glossaries, footnotes, summaries , and color illustrations, Reinforces reader understanding with additional materials, and end-of-chapter problems Discusses protein structure, folding and the bioengineering of cells, tissues and organs, pharmaceutical delivery systems using hydrogels, nanospheres, liposomes, and amino clay.